Comparação da taxa de sucesso de desmame ventilatório entre os índices integrativos de desmame e desmame convencional em pacientes neurocríticos em ventilação mecânica internados em UTI - Escobar, Ariel Aline Jardim Alves (2019)
Introduction: The importance of using a reasoned protocol is well known in the use of integrated predictive indices of weaning from mechanical ventilation (MVD) in neuropathic patients, as they can increase their MVD success rate. Objective: Compare the success rates of ventilatory weaning between the integrative and conventional. Methods: Randomized cohort study with 7 neurocritical patients, admitted to the ICU of a hospital on the western border of RS. Participants were divided into 2 groups, one as conventional ventilation weaning and the other as ventilatory weaning based on the use of integrative indexes Results: Four and three individuals completed the protocol in the integrative and conventional weaning groups, respectively. The time of mechanical ventilation (p = 0.81) and the length of hospital stay (p = 0.93) were not significant. There was an increase in the value of the rapid breathing index and superficial (p = 0.0001) and CROP (p = 0.004) after the intervention of the weaning group integrative. We did not find any significant value in the correlations between time of mechanical ventilation and ICU admission for Pão2 / FIO2, IRRS, CROP, IWI and TIE. Conclusion: There is no difference between the use of predictive weaning rates in relation to conventional weaning in the success rate of ventilatory weaning and duration of hospitalization in neuropathic patients.